Seismicity of the Bora‐Tullu Moye Volcanic Field, 2016–2017. (1st February 2019) - Greenfield, Tim; Keir, Derek; Kendall, J.‐Michael; Ayele, Atalay
Abstract: The Bora‐Tullu Moye (TM) volcanic field is a geothermal energy prospect in the central Main Ethiopian Rift, but little is known about the seismicity of the region. Here we document seismic activity between February 2016 and October 2017, locating more than a 1, 000 seismic events of local magnitude 0 to 2.7. This provides new insights into fluid movement and deformation beneath what we only now realize is a complicated volcanic system. A discrete cluster of events lies beneath TM, but, surprisingly, most of the seismicity lies in two clusters that are beneath neither the Bora or TM edifices. In these regions, we use earthquake cluster orientations, fault plane solutions, and fast seismic shear‐wave orientations to show that seismicity is triggered by hydrothermal circulation of fluids along preexisting fractures. The fractures trend in multiple directions and are, in general, not parallel to rifting related structures. Instead, the fractures are parallel to structures created during previous caldera forming eruptions at both Bora and TM. Highly fractured regions such as this could be attractive targets for geothermal power generation. We estimate a minimum depth for a magmatic body beneath TM to be 6.5 km using the mapped brittle‐ductile transition. Frequency analysis of the earthquake waveforms reveal the bulk of the events to be volcano tectonic, but some low‐frequency seismicity is present at a depth of 5 km beneath the TM edifice triggered by high pore fluid pressures. Key Points: More than 1, 000 earthquakes are detected and located around Tullu Moye, a volcano in the Main Ethiopian Rift Earthquakes locate to depths less than 6.5 km and cluster onto multiple orientations of faults where hydrothermal fluids are channeled Shear‐wave‐splitting observations and fault plane solutions indicate a rift parallel stress field locally affected by volcanic structures